Slow westward movement of salinity anomalies across the tropical South Indian Ocean - Vargas-Hernández , José Mauro (2015)
Decadal salinity variability is an important characteristic of the ocean. It characterizes differences in evaporative and precipitation fluxes at the surface, and in the subsurface it contributes to steric sea level change and freshwater/salt transports. In this paper, we identify and describe westward moving and decadally varying salinity anomalies within the thermocline of the tropical South Indian Ocean (SIO) based on ocean state estimates from the Simple Ocean Data Assimilation version 2.2.4 (SODA). This signature in the salinity anomalies is expressed at the depth of 20°C isotherm (D20). A two-dimensional radon transform quantifies the westward speeds as being between 0.4 and 1.7 cm s-1. These speeds are slower than those of first baroclinic-mode Rossby waves or mean advection speeds of the background flow in the same regions. The decadal salinity anomaly originates in the subtropical eastern SIO ( 39% of the variance explained) and merges with remote anomalies from the western tropical Pacific Ocean (WTPO) via the Indonesian Seas ( 11% of the variance explained). The eastern SIO displays both decadal ( 10-15 years) and interdecadal ( 15-30 years) variability influenced by the WTPO, whereas the decadal variability in the western SIO seems to be more influenced by signals originating in the subtropical eastern SIO. We conclude that these salinity anomalies are consistent with signatures of nonlinear baroclinic disturbances as explained in the recent literature, and possible interaction of higher order baroclinic-mode Rossby waves with the mean flow.